Systematic Review: Analisis Hubungan Pertumbuhan Ekonomi dan Tingkat Kemiskinan di Kabupaten Buton - Purnama; Herianto, Herianto; Nurdin, Nurdin; Hasirun, Darmin (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This study aims to analyze the relationship between economic growth and poverty levels in Buton Regency using a systematic literature review approach based on PRISMA guidelines. Although economic growth is often assumed to reduce poverty through increased employment and income, the results of this study show that in Buton Regency, significant economic growth does not always correspond with a decrease in poverty levels. This study identifies several causes of poverty, including educational factors, unemployment, population size, and inequality. Meta-analysis found three patterns of the relationship between economic growth and poverty: economic growth that reduces poverty, increases poverty, or has no significant impact on poverty. These findings indicate that economic growth in Buton Regency needs to be balanced with more inclusive policies focusing on poverty reduction, especially in the most vulnerable sectors. This study suggests the importance of implementing more equitable and fair development strategies to reduce economic and social disparities in Buton Regency.